2021
DOI: 10.1101/2021.04.11.21255231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptability of human papillomavirus (HPV) self-sampling among never- and under-screened Indigenous and other minority women: a randomised three-arm community trial in Aotearoa New Zealand

Abstract: Background: Internationally, self-sampling for human papillomavirus (HPV) has been shown to increase participation in cervical-cancer screening. In Aotearoa New Zealand, there are long-standing ethnic inequalities in cervical-cancer screening, incidence, and mortality; particularly for indigenous Māori women, as well as Pacific, and Asian women. Methods: We invited never- and markedly under-screened (≥5 years overdue) 30-69-year-old Māori, Pacific, and Asian women to participate in an open-label, three-arm, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The three trial arms were as follows: usual care , in which women were invited to attend a clinic for a standard smear sample; clinic‐based self‐testing , in which women were invited to take a self‐test at their usual general practice; and mail‐out self‐testing , in which women were posted a kit and invited to take a self‐test at home. This showed that, although screening uptake was lower than in the first RCT, self‐testing uptake was again statistically significantly preferred over usual care, with the highest participation in the mail‐out self‐test arm 13 …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The three trial arms were as follows: usual care , in which women were invited to attend a clinic for a standard smear sample; clinic‐based self‐testing , in which women were invited to take a self‐test at their usual general practice; and mail‐out self‐testing , in which women were posted a kit and invited to take a self‐test at home. This showed that, although screening uptake was lower than in the first RCT, self‐testing uptake was again statistically significantly preferred over usual care, with the highest participation in the mail‐out self‐test arm 13 …”
Section: Introductionmentioning
confidence: 89%
“…All Māori, Pasifika and Asian women who were invited to take part in one of the two self‐testing arms of the RCT 13 were given a survey to complete about their experience of self‐testing, which they completed at home or in the clinic, depending on where they completed the self‐testing. The women were all aged 30‐69 years, were resident in Waitematā or Auckland District Health Board (DHB) areas and had never been screened or were overdue (≥5 years) for cervical screening.…”
Section: Methodsmentioning
confidence: 99%